Inclusion of third-person perspective in CAVE-like immersive 3D virtual reality role-playing games for social reciprocity training of children with an autism spectrum disorder - Tsai, Wei-Te; Lee, I-Jui; Chen, Chien-Hsu (Universal access in the information society, 2021)
The present study aimed to improve the ability of children with autism to recognize emotions correctly. We used our third-person perspective role-playing game (TPP-RPG) method to teach social skills and help develop an improved understanding of the six basic emotions. The experiment was divided into two phases: The first involved working with traditional figure card emotional recognition and the second involved a subject entering a 3D cave automatic virtual environment (CAVE) to engage with interactive games. While the traditional graphic card is a static picture that represents one of the six basic human emotions, the virtual reality of CAVE-like immersive 3D role-playing games enables the use of actual picture scene syntheses plus the animation of 3D characters to express emotions. The participating children were instructed to role-play with (1) three-dimensional (3D) virtual role animations and observe (2) two different real-time switchable role-play animations of themselves and their counterpart socially interacting. This single-subject study was based on multiple-baseline, across-subject design and involved 5 weeks of TPP-RPG training intervention. From this research activity, we found that the role-play performance of all three participants rose substantially during the intervention phase and remained significantly higher in the maintenance phase compared to their baseline levels.